Specific administrative act in polish administrative law and church particular administrative acts in canon law – legal-comparative analysis - Główczewska, Aleksandra; Rokicka-Murszewska, Karolina (Prawo Kanoniczne, 2020)
The article aims to discuss the main features of church particular administrative acts and compares them with administrative acts known in polish administrative law. There will be analysed important aspects of duties division and Church authority competence. Authors will approximate definition of church administrative act and examine appropriate canon law provisions. The main assumption of the article is to indicate common features of administrative acts in canon and administrative law.